Inequality, emulation and debt: The occurrence of different growth regimes in the age of financialization in a stock-flow consistent model. Issue 2 (3rd April 2018) - Detzer, Daniel
ABSTRACT: In the era of financialization, increasing income inequality could be observed in most developed and many developing countries. Despite similar developments in inequality, the growth performance and drivers for growth differed markedly among countries, allowing clusters of different growth regimes to be identified. Among them are 2 extreme types: the debt-led private-demand boom and the export-led mercantilist economies. Whereas the former rely mainly on credit-financed household consumption in order to compensate for the potential lack of demand (associated with the depressing effect of financialisation), the latter rely on net exports as the main driver of aggregate demand. Using a stock-flow consistent model it will be demonstrated how increasing inequality, depending on a countries institutional structure and regulatory framework, affects growth differently, explaining the occurrence of both regime types.